Determination of Priorities for the Development of Small and Medium Enterprises in the Province of South Sulawesi Using the Weighted Product Model - Nur Annisa Safitri Yusuf; Mustikasari Mustikasari; M. Hasrul H (Journal of Computer Engineering, Electronics and Information Technology, 2023)
Small and Medium Enterprises (SMEs) are a sector that plays a vital role in running the national economy. The South Sulawesi Provincial Office of Industry as a regional government organization is tasked with administering affairs in the industrial sector of the South Sulawesi Province. In terms of developing SMEs, the South Sulawesi Provincial Industry Service has the right to determine priority industries that have the potential to be developed. The decision-making process at the South Sulawesi Industry Office is still experiencing several obstacles. This is due to the decision making does not use an objective method. In order to help solve this problem, we need a system that can be used to determine industrial development priorities. This research builds a web-based decision support system software regarding priority setting for SMEs development in South Sulawesi Province using the weighted product model. A method that will find a concluding solution by considering industry weights and criteria. This study uses the implementation of the data management subsystem using MySQL. Meanwhile, the implementation of the model management subsystem uses the weighted product model and the dialog management subsystem uses a website interface that can assist the South Sulawesi Provincial Office of Industry in determining priorities for the development of SMEs.